Is This Information Source Commercially Biased? How Contradictions Between Web Pages Stimulate the Consideration of Source Information. Issue 5 (3rd July 2016) - Kammerer, Yvonne; Kalbfell, Eva; Gerjets, Peter
Abstract : In two experiments we systematically examined whether contradictions between two web pages—of which one was commercially biased as stated in an "about us" section—stimulated university students' consideration of source information both during and after reading. In Experiment 1 "about us" information of the web pages was presented below their content; in Experiment 2 it needed to be accessed by clicking on an "about us" link. Results of both experiments showed that after having encountered contradicting information, students attended longer to the "about us" statements, more frequently included this information in their written reports, and judged the commercially biased page as less trustworthy and less convincing than after having encountered consistent (positive or negative) information. These findings as well as additional results regarding think-aloud data (Experiment 1) and click data (Experiment 2) are discussed in the light of the discrepancy-induced source comprehension assumption.